The Babylon complex: theopolitical fantasies of war, sex, and sovereignty - Runions, Erin (Fordham University Press, 2014)
Looks at the biblical figure of Babylon as it appears in U.S. culture from 2001-2011 in politics, media, war, and sexual regulation; analyzes allusions to Babylon as part of a larger response to the erosion of national sovereignty within economic globalization.